Peningkatan Efisiensi dan Efektifitas Layanan Dosen dalam Pemanfaatan Web Application - Reina Reina (Bina Nusantara University, 2013)
This study aims to determine the benefits of a web application in improving the efficiency and effectiveness of services to lecturers. The research method consists of literature study and data collection analysis based on observations. Implementing a web application, an observation is conducted followed by a comparison on data prior to the implementation. The evaluation results show that the implementation of a web application improves efficiency and effectiveness in the use of time and resources in providing services to lecturers in information access.